STUDI STRATEGI PENINGKATAN KINERJA GABUNGAN PERKUMPULAN PETANI PEMAKAI AIR (GP3A) DALAM MENGELOLA JARINGAN IRIGASI PADA DAERAH IRIGASI TINDAKI KABUPATEN PARIGI MOUTONG - Idran, Idran (Katalogis, 2015)
This research aimed at to find out the status and strategy of Water User Association Federation (WUAF) perfomance increasing on Irrigation Schemes Management at Tindaki Irrigation Area of Parigi Moutong Regency. The population of the research is water users that included in WUAF which consist of 165 farmers , and there is 62 respondent that choosed by using proporpotional random sampling. The research type is desctriptive with quantitative approach. Data collected through questionaire, observation and documentation. Data analyzed by SWOT analysis. The result of this study indicate the status of WUAF perfomance is in Poor level (26%-50%), consist of Organization Aspect in Good level (50%-58,31%), Water Supply aspect in Good level (50%-75%), Maintenance aspect in Poor level (0%-25%%), Financial aspect in Poor level (43,75%-50%), Present condition of Irrigation Schemes aspect in Poor level (47,25%-50%) and Technical empowerment aspect ini Good level (52,75%-75%), 2). The strategy to increase WUAF perfomance is Strength – Opportunity (SO) strategy that use strength to make use of opportunity through : (i) strengthening the capacity of WUA, (ii) Legalization of WUA support into Qualified of other WUA members (farmers), (iii) WUA must be learned in the network-information system, (iv) The WUA’s capacity building by Government must be in the farmer-need assesment preparation.